BUDAYA ORGANISASI, MOTIVASI, DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DINAS LINGKUNGAN HIDUP KABUPATEN WONOGIRI - Dwi Dian Putra Prasetio; Istiatin Istiatin; Sri Hartono (ITB AAS INDONESIA Surakarta, 2019)
The aim of this research are 1) to find out the simultaneous influence between organizational culture, motivation, and communication on the employee productivity of the environmental services in Wonogiri Regency, 2) to determine in partial organizational culture, motivation and communication the effect on the employee productivity of the environmental services in Wonogiri Regency. The population in this study were all employees at the Wonogiri Regency Environmental Agency, which numbered 286 employees. The samples in this study were 86 respondents. Data collection techniques in this research were using observation, documentation, and questionnaires. Technical data analysis in this research were using classic assumption test, multiple linier test, t test, f test, the coefficients determined. The result of this study: 1) There is a simultaneous influence of organizational culture, motivation, and communication on the work productivity of Wonogiri District's environmental officers. 2) in partial variable organizational culture, motivation and communication give significant effect on employee productivity of the of the environmental services in Wonogiri Regency. Keywords : organizational culture, motivation, communication, employee productivity.